MORPHOLOGICAL FEATURES OF INDUSTRIAL HEMP CULTIVATION IN SOIL AND CLIMATIC CONDITIONS OF SYRDARYA REGION (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
This article describes that in 2024, research was carried out on the cultivation of technical hemp in the soil and climatic conditions of the Khavast district of the Syrdarya region, where 4 variety samples were studied in comparison with the standard variety Rodnik, which, with sufficient irrigation and compliance with agricultural cultivation technology, it is quite possible to successfully cultivate. Breeding work was carried out by the method of individual selection of industrial hemp plants with the necessary improved characteristics for further research in order to create new local varieties for our Republic.